Pembelajaran Kewirausahaan Sebagai Pencetak Young Entrepreneur di Madarasah Aliyah Al Iman Adiwerna - Nurizzatul Maula; Aziz Awaludin; Muntaqo, Arif; Agung Maulana, M; Syafiq, Muhammad; Sakinatun Baity, Nur; Mahdiyana, Rima (SETYAKI : Jurnal Studi Keagamaan Islam, 2024)
Education plays a key role in the development of a nation, with an important contribution both through formal and informal channels such as the family. Formal education in institutions such as schools aims to expand knowledge and critical thinking skills, while informal education in the family functions as an initial foundation for the development of a child's character. In Indonesia, as regulated in Constitution No. 20 of 2003, education is a planned effort to develop individual potential so that they are ready to face social and economic challenges. In the context of economic development, entrepreneurship is a central issue with the government encouraging the growth of new entrepreneurs to create jobs and increase competitiveness. It is hoped that entrepreneurship education can overcome the obstacles faced by young people, such as uncertainty in choosing the type of business and the risk of failure. Entrepreneurship learning not only includes the theory of starting a business but also marketing strategies and developing creative ideas. Thus, entrepreneurship education functions as a tool to improve the skills, creativity and readiness of young entrepreneurs in facing global competition. Evaluation of effective learning models will make a significant contribution in producing a generation of competitive and innovative entrepreneurs.